Bimbingan Teknis Pemanfaatan Pekarangan sebagai Lumbung Pangan Keluarga - Musdalifah, Nurul; Khairi Barus, Rizki Al; Resubun, Mariana Lusia; Kusumah, Rangga; Adrianus, Adrianus; Anwar, Anwar; Yusuf, Mani; Djaja, Irba; Ekowati, Nurhening Yuni; Sembiring, Jefri (Universitas Pahlawan Tuanku Tambusai, 2025)
Dharma Wanita Persatuan (DWP) Wasur National Park is an association of civil servant wives who play an important role in women's empowerment, particularly in supporting food security and improving household economies. These efforts are carried out through the utilization of small plots of land and the processing of kitchen waste into liquid organic fertilizer (POC) and plant-based pesticides. Training activities were conducted using lectures, question and answer sessions, practical demonstrations, and direct discussions with participants. From this series of activities, DWP members gained knowledge and skills in processing kitchen waste into useful products. The utilization of kitchen waste into POC and plant-based pesticides is a simple yet highly impactful step, as it not only helps reduce the volume of household waste but also adds value to the environment. Vegetable scraps, fruit peels, and food residues can be transformed into products that support environmentally friendly agriculture. Through this activity, DWP members can become more empowered in managing household waste while producing useful products to support food self-reliance and enhance family economic value.